Tauhid INTEGRASI WAHYU DAN AKAL UNTUK MEMBANGUN ARGUMEN YANG KOKOH BIDANG ILMU KALAM - Renata, Tiara (Bahasa Indonesia, 2025)
This paper examines how the relationship between reason and revelation contributes significantly to the construction of arguments in the treasury of theology. This study uses a library research approach, namely by collecting sources from relevant primary and secondary literature. The data obtained are then analyzed using descriptive-analytical methods to obtain a comprehensive understanding. The results of this study reveal three important points: first, reason has a noble place in the Qur'an, as seen from various verses that encourage humans to think. Second, in the theological dimension, there is a difference in emphasis between reason and revelation, as seen in the Mu'tazilah school which prioritizes reason, while the Ash'ariyah places revelation in the main position with a more limited role for reason. Third, in the views of Muslim philosophers such as Ibn Rushd and al-Kindi, reason and revelation are not opposed, but are seen as two sources of knowledge that complement each other and are harmonious.